MicroRNA and Nonsense Transcripts as Putative Viral Evasion Mechanisms - Bakre, Abhijeet A.; Maleki, Ali; Tripp, Ralph A. (Frontiers in Cellular and Infection Microbiology, 2019)
Viruses use various evasion strategies to overcome host defenses and aid their replication. We propose that RNA viruses use a passive means to elude host anti-viral responses based on complementarity of the viral genomic and associated transcript sequences that mimic or inhibit microRNAs (miRNAs). By hindering the complementarity between the miRNA seed site and the miRNA recognition element, a virus may alter host gene expression and the global landscape regulated by miRNAs. This theory is supported by computational analysis of several paramyxovirus genomes with sequence motifs that are identical or complementary to host miRNA seed sites typically located at the 5’ end of the mature miRNA. Viral miRNA may mimic host miRNAs enabling modification of the host network. It is possible that viral miRNA mimics can modify miRNA activity and foster suppression, while viral miRNA seed sponges operate to inhibit miRNA function and lead to increased gene expression. Identifying the mechanisms in the network of interactions between host and viral transcripts can help determine ways to improve vaccine efficacy, aid therapeutics, and potentially mitigate the adverse events associated with some vaccines.